Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3354/esr00315
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale sexual segregation of bowhead whales

Abstract: Skin biopsy samples from 806 bowhead whales Balaena mysticetus collected between 1995 and 2010 at 4 locations in Nunavut, Canada, and at 1 locality in West Greenland were used for determination of sex and sexual segregation of bowhead whales in the Baffin Bay stock. There was a significant dominance of females in the Disko Bay samples (78%), whereas the sex ratio in aggregations in Nunavut was not significantly different from 50:50. Data on the body length of whales suggest that primarily large mature whales w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…Genetic analysis of skin biopsies from bowhead whales in Disko Bay revealed a large proportion of females (81%) similar to those found in previous studies (Heide-Jørgensen et al, 2010;Wiig et al, 2011;Rekdal et al, 2015). The explanation for the sex segregation remains unresolved although it has been suggested that Disko Bay is used by post-lactating, pregnant, or resting females to regain fat deposits that are otherwise more energetically demanding to acquire in other areas (Heide-Jørgensen et al, 2010). The fact that the data in this study are derived mainly from adult females is important when interpreting the results since juvenile bowhead whales may exhibit different dive and foraging behaviour.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Genetic analysis of skin biopsies from bowhead whales in Disko Bay revealed a large proportion of females (81%) similar to those found in previous studies (Heide-Jørgensen et al, 2010;Wiig et al, 2011;Rekdal et al, 2015). The explanation for the sex segregation remains unresolved although it has been suggested that Disko Bay is used by post-lactating, pregnant, or resting females to regain fat deposits that are otherwise more energetically demanding to acquire in other areas (Heide-Jørgensen et al, 2010). The fact that the data in this study are derived mainly from adult females is important when interpreting the results since juvenile bowhead whales may exhibit different dive and foraging behaviour.…”
Section: Discussionsupporting
confidence: 74%
“…However, binned data allowed for long-term data collection from areas where it would otherwise be impossible to gather information on diving behaviour of bowhead whales. Genetic analysis of skin biopsies from bowhead whales in Disko Bay revealed a large proportion of females (81%) similar to those found in previous studies (Heide-Jørgensen et al, 2010;Wiig et al, 2011;Rekdal et al, 2015). The explanation for the sex segregation remains unresolved although it has been suggested that Disko Bay is used by post-lactating, pregnant, or resting females to regain fat deposits that are otherwise more energetically demanding to acquire in other areas (Heide-Jørgensen et al, 2010).…”
Section: Discussionsupporting
confidence: 62%
“…Sex of the whales was determined from skin biopsies collected simultaneously with the instrumentation following genetic methods described in [1].…”
Section: Methodsmentioning
confidence: 99%
“…Why bowhead whales (Balaena mysticetus), primarily females without calves, spend time in Disko Bay, West Greenland in spring [1][2][3] is unknown. High vocalization rates suggest the area is a mating ground [4]; however, there are few males suggesting that there may be other explanations for whales spending time there.…”
Section: Introductionmentioning
confidence: 99%
“…For example, prey densities or sizes required for feeding by adult males may be quite different than for reproductive females, and these differences can drive changes in the spatial distribution of the population (e.g. Le Boeuf et al 2000, Engelhaupt et al 2009, Heide-Jørgensen et al 2010.…”
Section: Reproductionmentioning
confidence: 99%